Problems and challenges for ontology integration in the SemanticWeb - Gómez, Sergio Alejandro (2006)
The Semantic Web is a future vision of the current web in which the resources have exact meaning. The meaning of resources is given by means of ontology definitions. When these ontologies are defined in isolation, the union of two or more ontologies can result in inconsistencies. Resolving such inconsistencies in order to put the ontologies into mutual agreement is known as ontology integration. In this paper, we briefly survey the languages for representing information in the web and the SemanticWeb. We also review some methodologies for performing ontology integration. Part of our current research is focused into providing alternative representations of current standards for defining ontologies in order to overcome the problems associated with the traditional methods for ontology integration.